Readiness of Pamantasan Ng Cabuyao Education Graduates in the Licensure Examination for Teachers: Basis for Intervention Program - Gabor, Edward Francis; Montillano, Allen Cris (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
The readiness of Pamantasan ng Cabuyao Education graduates for the Licensure Examination for Teachers (LET) is crucial in ensuring their success in obtaining professional certification. This study evaluates the cognitive strategies, key content knowledge, academic behaviors, and contextual skills that influence their preparedness. Utilizing an explanatory sequential mixed-methods approach, quantitative data were gathered through surveys to determine the extent of readiness to 145 PNC Education Graduates, while qualitative insights were collected from 6 participants randomly selected through interviews and focus group discussions. Findings revealed that graduates demonstrated strong motivation and adaptability in their preparation, but faced challenges in maintaining structured study schedules, mastering STEM subjects, and navigating external constraints such as financial limitations and work obligations. Significant differences in readiness were observed across academic programs, highlighting the need for targeted interventions. Based on these results, a comprehensive intervention plan is proposed, including a free review program, mentorship initiatives, and structured workshops focusing on problem-solving techniques and exam-taking strategies. This study underscores the importance of tailored academic support to bridge gaps and enhance graduates’ overall LET preparedness, contributing to institutional efforts in increasing licensure exam success rates.